Dynamic Stretching Warm-Up Protocols and Performance Outcomes in Horizontal Jump Athletes: Dynamic Stretching Warm-Up Protocols and Performance Outcomes in Horizontal Jump Athletes - Faraz Khan; Aqsa Shamim Ahmed; Mariam Jabeen; Muniba Ashfaq; Muhammad Anees Ahmed, (Dialogue Social Science Review (DSSR), 2025)
Dynamic stretching has gained attention as an effective warm-up strategy for athletes involved in explosive sports, such as horizontal jumping. This study investigates the impact of dynamic stretching warm-up protocols on the performance of horizontal jump athletes, focusing on key performance indicators including jump distance, takeoff speed, and agility. The investigation examines dynamic stretching versus traditional static stretching because research shows that static stretching causes a temporary power decrease in muscles. During eight weeks, researchers studied 20 horizontal jump athletes who completed dynamic stretching exercises in one group and traditional general warm-up moving exercises in the other group. The experiment measured performance through evaluation of standing long jump distance, together with 30-meter sprint speed in pre-test and post-test conditions. The study demonstrates that practitioners who perform dynamic stretching achieve better athletic results with their jump distance performance, and their sprint times improved as well. Better movement efficiency, together with lowered injury risk, results from both temperature-enhanced muscles and more flexible joints, as well as neuromuscular activation produced by dynamic stretching. This research proves that dynamic stretching is better for horizontal jump athletes, because it not only increases their coordination but also enhances their muscle function before high-intensity activity. Dynamic stretching has to be integrated into a warm-up for performance enhancement routines as part of their routines for both professional athletes and their coaches. There is a need for new investigations to determine the proper stretching strategies that will yield the best performance with an acceptable reduction of accidents.